2016
DOI: 10.1111/mmi.13419
|View full text |Cite
|
Sign up to set email alerts
|

Non‐canonical roles of tRNAs and tRNA mimics in bacterial cell biology

Abstract: Transfer RNAs (tRNAs) are the macromolecules that transfer activated amino acids from aminoacyl-tRNA synthetases to the ribosome, where they are used for the mRNA guided synthesis of proteins. Transfer RNAs are ancient molecules, perhaps even predating the existence of the translation machinery. Albeit old, these molecules are tremendously conserved, a characteristic that is well illustrated by the fact that some bacterial tRNAs are efficient and specific substrates of eukaryotic aminoacyl-tRNA synthetases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 164 publications
(216 reference statements)
0
44
0
Order By: Relevance
“…tRNAs have also been found to play many diverse noncanonical roles, in particular in bacteria. Such roles include functions in the biosynthesis of diverse cellular macromolecules, and regulatory functions in which tRNAs are used as messengers or sensors for the metabolic state of the cell (Katz, Elgamal, Rajkovic, & Ibba, ). In addition to the emerging noncanonical roles of full‐length mncRNAs, fragments of mncRNAs, which are typically shorter and less highly structured than their full‐length precursors are increasingly reported to play cellular roles (Falaleeva & Stamm, ; Soares & Santos, ).…”
Section: Emerging Functions Of Mncrnamentioning
confidence: 99%
“…tRNAs have also been found to play many diverse noncanonical roles, in particular in bacteria. Such roles include functions in the biosynthesis of diverse cellular macromolecules, and regulatory functions in which tRNAs are used as messengers or sensors for the metabolic state of the cell (Katz, Elgamal, Rajkovic, & Ibba, ). In addition to the emerging noncanonical roles of full‐length mncRNAs, fragments of mncRNAs, which are typically shorter and less highly structured than their full‐length precursors are increasingly reported to play cellular roles (Falaleeva & Stamm, ; Soares & Santos, ).…”
Section: Emerging Functions Of Mncrnamentioning
confidence: 99%
“…Indeed, the TLD domain of tmRNA can resume translation on its internal coding sequence, even in the absence of any canonical initiation factors. The presence of structured RNA regions upstream of a coding sequence is one of the simplest mechanisms known for initiating translation, as observed today in many tRNA-like structures ( 60 , 61 ). In the same way, tmRNA also carries a signal for terminating translation on its internal reading frame.…”
Section: Origins Of Transfer-messenger Rnamentioning
confidence: 99%
“…Among these, tRNA-like structures (TLSs) are thought to be molecular fossils of the original RNA world. These structures are often located at the 3’-end of the single-stranded RNA genomes of many bacterial and plant viruses, allowing both for tRNA mimicry (including aminoacylation) and regulation of RNA genome replication ( 61 ). In an appealing ‘genomic tag model’, Weiner and Maizels ( 69 ) suggested that these 3′-terminal TLSs were molecular fossils that originally identified genomic RNA molecules for replication and also functioned as primitive telomeres.…”
Section: A Universal Proto-tmrna At the Origins Of Modern Trnas And Mmentioning
confidence: 99%
“…In addition, tRNAs and tRNA-derived fragments also serve regulatory roles in E. coli 1,2 and other bacteria (recently reviewed in refs. 3,4 ). For example, in E. coli , uncharged tRNA at the ribosomal A-site is the signal that stimulates RelA to produce guanosine tetraphosphate (ppGpp), which initiates the stress response to amino acid starvation.…”
Section: Introductionmentioning
confidence: 99%